Bigfoot, Cyclops, Yeti or just hype? - Abd Razak, Dzulkifli (2006)
YES, the Johor Government wants to get to the bottom of the Bigfoot mystery. Bigfoot has managed to evade capture and has instead captured headlines. So far, all evidence of Bigfoot’s existence has been unpersuasive. The Bigfoot mania is not new. Humanoid apelike creatures have been sighted for centuries in many parts of the world. In the forests of North America, there have been sightings of Skunk Ape, Momo, Grassman and Woods Devil. One of the earliest sightings of the footprints was in 1811 by a Canadian trader in Alberta. By the 1950s, the sightings were said to be almost regular. There are also similar tales of mythical giant apes in the oral traditions of Europe.